Cutoff values of body mass index for severe obesity in Korean children and adolescents: the 99th percentile versus 120% of the 95th percentile - Jaewon Choe; Jaehyun Kim; Jin Soo Moon (Korean Society of Pediatric Endocrinology, 2023)
Purpose Several definitions for severe obesity have been used, primarily the 99th percentile of the body mass index (BMI) and 120% of the 95th BMI percentile. This study aimed to establish a standardized definition for severe obesity in children and adolescents in Korea. Methods The 99th BMI percentile line and 120% of the 95th BMI percentile line were constructed using 2017 Korean National Growth Charts. To compare these 2 cutoff points for severe obesity, we included 9,984 individuals (5,289 males and 4,695 females) aged 10-18 years with anthropometric data available from the Korean National Health and Nutrition Examination Survey 2007-2018. Results Although 120% of the 95th percentile of BMI is widely used as a definition of severe obesity, the 99th percentile is almost identical to 110% of the 95th percentile in Korea, according to the latest national BMI growth chart for children and adolescents. The prevalence rates of high blood pressure, high triglycerides, low high-density lipoprotein cholesterol, and high alanine aminotransferase in the participants whose BMI was ≥120% of the 95th percentile were higher than in those whose BMI was ≥99th percentile (P<0.001). Conclusions A cutoff value for severe obesity of ≥120% of the 95th percentile is appropriate in children and adolescents in Korea. To provide follow-up care for severely obese children and adolescents, it is necessary to add a new line at 120% of the 95th percentile to the national BMI growth chart.